2012
DOI: 10.1097/iae.0b013e31821c3ee0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Retinal and Vitreous Temperature in Vitrectomy

Abstract: During routine vitreous surgery, the vitreous cavity and retina are cooled to much lower temperatures than those used in therapeutic hypothermia. Rapid rewarming occurs within the eye once the infusion line is closed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 6 publications
3
19
0
Order By: Relevance
“…5 . The strict measurements taken of retinal temperature immediately adjacent to the fovea by Landers et al during surgery were as follows: before vitrectomy, 34.9°C; at the end of vitrectomy after plugging the sclerotomies and closing the infusion line for 5 min, 32.6°C [ 14 ]. This difference of 2.3°C may have been enough to decrease VEGF-A expression in the eye, as our present results revealed that a 2°C decrease caused a significant decrease in VEGF-A expression in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 . The strict measurements taken of retinal temperature immediately adjacent to the fovea by Landers et al during surgery were as follows: before vitrectomy, 34.9°C; at the end of vitrectomy after plugging the sclerotomies and closing the infusion line for 5 min, 32.6°C [ 14 ]. This difference of 2.3°C may have been enough to decrease VEGF-A expression in the eye, as our present results revealed that a 2°C decrease caused a significant decrease in VEGF-A expression in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Romano et al measured and compared intraocular temperatures during surgery and found that the temperature within the anterior chamber was 23.6°C [ 13 ]. The retinal temperatures immediately adjacent to the fovea before and after vitrectomy were 34.9 and 32.6°C, respectively [ 14 ]. Retinal temperature just after vitrectomy is 2.3°C lower than before vitrectomy with the eyelid open, suggesting that the difference may be induced by cooling mediated by outside air and an anatomical alteration in the vitreous cavity after vitrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…After closing the infusion line, intraocular tissue rewarms rapidly [29, 30]. These temperature fluctuations could influence many biological functions like bleeding, expression of cytokines in the vitreous, induction of specific patterns of proteins, and neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the in vivo temperature of the vitreous cavity may range from 33.98C to 36.68C, with a likely temperature gradient existing. 41,42 For this reason, the T 1 relaxation times measured from the phantom porcine vitreous and BSS were temperature corrected to 358C to simulate, as accurately as possible, the temperature in the mid vitreous cavity. Similarly, when calibrating the T 1 times for either vitreous or aqueous, the assumption was made that the patients' mid vitreous cavity temperature at the time of their scans was 358C.…”
Section: Discussionmentioning
confidence: 99%